Kepuasan bekerja di kalangan Pegawai Tadbir Universiti Putra Malaysia, Serdang, Selangor - Mohd Noah, Sidek; Muhamad, Mardiana (Universiti Putra Malaysia Press, 1999)
The purpose of this study was to identify the existence of correlation between job satisfaction aspects such as working environment, promotion, salary, supervision and colleagues with job satisfaction amongst UPM's Administration Officers. The subjects of this study who consisted of 55 Administration Officers, who worked with UPM until January 1998 were selected using simple random sampling. The instrument used in this study was the Job Descriptive Index (JDI) which was translated into Bahasa Melayu by Arinn Haji Zainal (1980) using back translation technique. The data obtained were then analysed using the descriptive statistic, simple regression and multiple regression at .05 level of significance. The results of the study revealed that there was a correlation between working environment, promotion, salary, supervision and colleagues with job satisfaction. The result also revealed that each of the aspects namely the working environment, promotion, salary, supervision and colleagues had a significant influence on job satisfaction. Based on the implications of the research findings, several recommendations were put forward.